EFFORTS TO IMPROVE STUDENTS FIGURAL CREATIVITY THROUGH THE USE OF 5E LEARNING CYCLE WITH INTERRELATIONSHIP DIAGRAM ON REVIEW OF VERMES CLASS X-8 SMA NEGERI 3 SURAKARTA ACADEMIC YEAR 2012/2013 - Joko Ariyanto, Artha Vinsentricia, Suciati Sudarisman (Pendidikan Biologi, 2015)
The purpose of the research is to increase the figural creativity of students through the implementations of 5E Learning Cycle with Interrelationship Diagram in students of X-8 class SMA Negeri 3 Surakarta school years 2012/ 2013.This research was a Classroom Action Research with three cycles of action. Each cycle consisting of four phases which are plan, action, observation, and reflection. The observational subject was the students of X-8 class SMA Negeri 3 Surakarta school years 2012/2013 amounting 32 students. The source of data comes from teacher and students. The observational data were obtained from the observation, interview and documentation. Data validation observation is using the methods of triangulation observer. Technical analysis of data was using qualitative descriptive. Research procedures were using interrelated spiral model.Result of the research showed that using 5E Learning Cycle with Interrelationship Diagram can increase figural creativity of students from pre cycle to first cycle, from first to second cycle, and second to third cycle. The process of learning was not fully and independently accomodating pre cycle students, so that the students were lack in expressing, developing, and linking the idea of the materials. Cycles I and II were not reaching the target. Then, in Cycle III there was an improvement so that be able to aim the target.The conclusion based on the result above is that 5E Learning Cycle with Interrelationship Diagram can increase figural creativity of the students of X-8 class SMA Negeri 3 Surakarta school years 2012/ 2013.Keywords : 5E Learning Cycle, Interrelationship Diagram (ID), figural creativity